The Chromosome-Scale Genomes of Exserohilum rostratum and Bipolaris zeicola Pathogenic Fungi Causing Rice Spikelet Rot Disease - Ke He; Chenyu Zhao; Manman Zhang; Jinshao Li; Qian Zhang; Xiaoyi Wu; Shan Wei; Yong Wang; Xujun Chen; Cheng Li (Journal of Fungi, 2023)
Rice spikelet rot disease occurs mainly in the late stages of rice growth. Pathogenicity and biological characteristics of the pathogenic fungus and the infestation site have been the primary focus of research on the disease. To learn more about the disease, we performed whole-genome sequencing of Exserohilum rostratum and Bipolaris zeicola for predicting potentially pathogenic genes. The fungus B. zeicola was only recently identified in rice.We obtained 16 and 15 scaffolds down to the chromosome level for E. rostratum LWI and B. zeicola LWII, respectively. The length of LWI strain was approximately 34.05 Mb, and the G + C content of the whole genome was 50.56%. The length of the LWII strain was approximately 32.21 Mb, and the G + C content of the whole genome was 50.66%. After the prediction and annotation of E. rostratum LWI and B. zeicola LWII, we predicted that the LWI strain and LWII strain contain 8 and 13 potential pathogenic genes, respectively, which may be related to rice infection. These results improve our understanding of the genomes of E. rostratum and B. zeicola and update the genomic databases of these two species. It benefits subsequent studies on the mechanisms of E. rostratum and B. zeicola interactions with rice and helps to develop efficient control measures against rice spikelet rot disease.